Assessment of Employability Skills of Technical-Vocational Education and Training (TVET) Graduates: Basis for an Enhancement Program - Mariano, Rayhanah P.; Tantoco, Luzviminda F. (International Journal of Multidisciplinary: Applied Business and Education Research, 2023)
The study aims to determine the employability skills of Technical-Vocational Education and Training Graduates of Valenzuela City Polytechnic College. This study was carried out to 423 graduates of TVET using convenience sampling and forty-five (45) employers who were selected purposively in the City of Valenzuela. The respondents had completed the TVET program. A survey questionnaire, document analysis and an interview guide were used. Frequency, percentage, and weighted mean were utilized in the statistical analysis and handling of the data. Among 423 TVET graduates of ValPoly from 2015 to 2019, majority are employed which had an employment rate of 87.94 percent, compared to a rate of 12.06 percent for those who were unemployed. Carpentry obtained the highest employment rate while the bread and pastry production got the lowest employment rate. The year 2019 also has the highest rate while respondents who graduated in 2016 have the lowest employment rate. Half of the employed graduates acquired a "regular status". Despite the skills mismatch, graduates have managed to seek employment related to their training right after graduation. Communication skills is the most useful skill in the workplace. ValPoly has provided comprehensive and effective programs and provisions that enhance graduates' employability skills. TVET graduates employed were assessed as highly competent by their employers. Several factors that facilitate the acquisition of employment. A proposed enhancement program for the employability skills of TVET graduates is formulated based on findings of this study to ensure that all graduates will be equipped with skills for employment.